(untitled) (American Journal of Pedagogical and Educational Research, 2023)
In the article, the status of each species according to the international red book, i.e. IUCN, of the plants included in the red book distributed in the Nurota State Reserve, was given, and the GeoCAT method was used directly. We converted the data of each species into a CSV file, as a result, the EOO of each species, i.e., the area where the species is spread, and the AOO, the areas where the species can spread, were determined. The research results show that every plant kept wild should be protected from anthropogenic influence and special protection measures should be developed.